Synthesis of Biaryl Derivatives via a Magnetic Pd-NPs-Catalyzed One-Pot Diazotization–Cross-Coupling Reaction - Zong, Yan; Hu, Jiefeng; Sun, Peipei; Jiang, Xiaoqing (Synlett, 2012)
A magnetic Pd-NPs-catalyzed one-pot diazotization–cross-coupling reaction of anilines and arylboronic acids was developed. Biaryl derivatives were therefore synthesized in good to excellent yields. Through magnetic separation, the catalyst could be recovered and reused for five times. There were several obvious advantages such as broad applicability, high selectivity, simply experimental operation as well as the convenient preparation, high efficiency and reusability of catalyst.
Keywords: nanopalladium; catalysis; diazotization; cross-coupling; magnetic separation